ҚАРАҚАЛПАҚ МУЗЫКА КӨРКЕМ ӨНЕРИ ТАРИЙХЫНДА СИМФОНИЯЛЫҚ ОРКЕСТРДИӉ РАЎАЖЛАНЫЎ БАСҚЫШЛАРЫ - Алланбаев, Р. (НАУКА и ОБЩЕСТВО, 2022)
The article tells about the stages of symphony orchestra development in the history of Karakalpak musical culture, the role of opera and musical drama performances staged at the Karakalpak State Musical Theater named after Berdakh, in the formation of a professional musical culture team in Karakalpakstan. Furthermore, there was also described history of the opening of the Nukus branch of the Uzbek State Conservatory and the role of the Khalq Sozlari Ensemble, the Khalq Sozlari Orchestra, the Symphonic and Chamber Orchestras in the education of young people were also discussed.
Keywords: опера; музыка; оркестр; композитор; история; музыкальная драма